PENGARUH JUMLAH SMU, JUMLAH GURU DAN JUMLAH RUANG KELAS TERHADAP JUMLAH MURID YANG TERDAPAT DI PROVINSI LAMPUNG - Brahmono, Boris; Idris, Muhammad; Wahyudi, Apri (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2017)
This study aims to determine whether there is influence that signikan between Number of High School , Number of Teachers and the number of students who are in the province of Lampung. This study uses a quantitative study using SPSS software to get results afterwards analysis. Data get from the Central Statistics Agency website Lampung Province. The result showed a marked influence between variables Number of Pupils with Variable Number of High School, Total Number of Classroom and number of Teachers and either partially or collectively – together.